Heterogeneity of mutational mechanisms and modes of inheritance in auriculocondylar syndrome. Issue 3 (12th January 2013) - Gordon, Christopher T; Vuillot, Alice; Marlin, Sandrine; Gerkes, Erica; Henderson, Alex; AlKindy, Adila; Holder-Espinasse, Muriel; Park, Sarah S; Omarjee, Asma; Sanchis-Borja, Mateo; Bdira, Eya Ben; Oufadem, Myriam; et al.
Abstract : Background: Auriculocondylar syndrome (ACS) is a rare craniofacial disorder consisting of micrognathia, mandibular condyle hypoplasia and a specific malformation of the ear at the junction between the lobe and helix. Missense heterozygous mutations in the phospholipase C, β 4 ( PLCB4 ) and guanine nucleotide binding protein (G protein), α inhibiting activity polypeptide 3 ( GNAI3 ) genes have recently been identified in ACS patients by exome sequencing. These genes are predicted to function within the G protein-coupled endothelin receptor pathway during craniofacial development. Results: We report eight additional cases ascribed to PLCB4 or GNAI3 gene lesions, comprising six heterozygous PLCB4 missense mutations, one heterozygous GNAI3 missense mutation and one homozygous PLCB4 intragenic deletion. Certain residues represent mutational hotspots; of the total of 11 ACS PLCB4 missense mutations now described, five disrupt Arg621 and two disrupt Asp360. The narrow distribution of mutations within protein space suggests that the mutations may result in dominantly interfering proteins, rather than haploinsufficiency. The consanguineous parents of the patient with a homozygous PLCB4 deletion each harboured the heterozygous deletion, but did not present the ACS phenotype, further suggesting that ACS is not caused by PLCB4 haploinsufficiency. In addition to ACS, the patient harbouring a homozygous deletion presented with central apnoea, a phenotype that has not been previously reported in ACS patients. Conclusions: These findings indicate that ACS is not only genetically heterogeneous but also an autosomal dominant or recessive condition according to the nature of the PLCB4 gene lesion.